Population structure of Annona coriacea Mart. (Annonaceae) in different Cerrado phytophysiognomies - Silva, Patrícia Oliveira da; Valente, Jessica Barros Cabral; Silva, Patricia Lacerda; Gomes, Carolina Ferreira; Menino, Gisele Cristina de Oliveira (Comunicata Scientiae, 2020)
Knowing the regeneration and structure of a species in different phytophysiognomies is extremely important to understand its pattern of occurrence. In spite of its importance, this type of study is still scarce in the Cerrado biome. In this perspective, this work aimed to compare the structure of the arboreal and regenerating strata of Annona coriacea in the cerrado sensu stricto and in the cerradão (savanna woodland). For that purpose, 13 plots of 400m² were installed in each physiognomy. All individuals of A. coriacea were sampled and had their diameter and height measured. The individuals were divided into regenerating and arboreal and were distributed in classes of height and diameter. Furthermore, the absolute density and the basal area of each extract were calculated in each physiognomy. The parameters were compared using the T-test. In total, 130 individuals of A. Coriacea were sampled, with 42 regenerating individuals in the cerrado sensu stricto and 49 in the cerradão. As for the arboreal individuals, 33 were sampled in the cerrado sensu stricto and 6 in the cerradão. All evaluated parameters revealed to be significantly different for the physiognomies. Based on these results, it is possible to affirm that A. coriacea did not present a distribution pattern in the two physiognomies, although it presents a better establishment success in the cerrado sensu stricto. In the cerradão, although the seeds can germinate, the seedlings fail to develop and reach the adult age.